The role of the huemul (Hippocamelus bisulcus) in Patagonian maritime hunter-gatherer strategies: The case of Diego Portales Island and ultima Esperanza inland sea (Chile) - Navarrete, Vanessa; Garcia-Piquer, Alberto; Garcia, Christian; Prieto, Alfredo; Pique, Raquel (My University, 2025)
The biodiversity of animal species in the ultima Esperanza inland sea (Magallanes region, Chile) provides an exceptional opportunity to study the economic and organizational strategies of maritime hunter-gatherer groups in the Fuego-Patagonian archipelago. The consumption of huemul (Hippocamelus bisulcus) in Southern South America is well documented since the Middle Holocene, although its role in the subsistence strategies of maritime hunter-gatherers varies depending on the geographical and environmental area. The aim of this paper is to assess the implications of huemul exploitation on organizational strategies by Late Holocene maritime hunter-gatherer groups from the ultima Esperanza inland sea (Magallanes region, Chile). In this work we present the results of a zooarchaeological analysis of the huemul assemblage from the sites of Bahia Easter 1 and Bahia Easter 2 (Diego Portales Island, ultima Esperanza, Chile). The results show the high importance of huemul in the maritime hunter-gatherer diet, and provide new insights into the hunting and transport strategies of this prey. Furthermore, the integration of the data within the local and regional archaeological record allowed us to identify similarities at the scale of the inland sea, where huemul was frequently exploited both in island and coastal environments in contrast to what is documented in the neighboring Skyring Sea and Otway Sea.
Keywords: zooarchaeology; animal resources; island environments; fuego-patagonia; late holocene